A new brain‐penetrant glucosylceramide synthase inhibitor as potential Therapeutics for Gaucher disease. Issue 3 (31st August 2021) - Fujii, Takahiro; Tanaka, Yuta; Oki, Hideyuki; Sato, Sho; Shibata, Sachio; Maru, Takamitsu; Tanaka, Yuta; Tanaka, Maiko; Onishi, Tomohiro
Abstract: Gaucher disease (GD), the most common lysosomal storage disorders, is caused by GBA gene mutations resulting in glycosphingolipids accumulations in various tissues, such as the brain. While suppressing glycosphingolipid accumulation is the central strategy for treating peripheral symptoms of GD, there is no effective treatment for the central nervous system symptoms. As glycosphingolipid biosynthesis starts from ceramide glycosylation by glucosylceramide synthase (GCS), inhibiting GCS in the brain is a promising strategy for neurological GD. Herein, we discovered T‐036, a potent and brain‐penetrant GCS inhibitor with a unique chemical structure and binding property. T‐036 does not harbor an aliphatic amine moiety and has a noncompetitive inhibition mode to the substrates, unlike other known inhibitors. T‐036 exhibited sufficient exposure and a significant reduction of glucosylsphingolipids in the plasma and brain of the GD mouse model. Therefore, T‐036 could be a promising lead molecule for treating central nervous system symptoms of GD. Abstract : Suppression of glycosphingolipids accumulations by inhibition of glucosylceramide synthase (GCS) is considered a promising therapeutic approach for Gaucher disease. However, there is no effective treatment for the central nervous system symptoms today. Here, we report discovery of a novel GCS inhibitor T‐036, which is potent, orally effective, and brain‐penetrant. T‐036 does not harbor an aliphatic amine moiety and has a non‐competitive, inhibitory binding mode to the substrates unlike other known inhibitors. T‐036 exhibited significant reduction of glycosphingolipids in the disease mouse model. Therefore, T‐036 could be a promising lead molecule for treating central nervous system symptoms of GD.